Disease-Specific Survival of AJCC 8th Stage II Gastric Cancer Patients After D2 Gastrectomy - Zheng, Xiaohao; Wu, Yunzi; Zheng, Li; Xue, Liyan; Jiang, Zhichao; Wang, Chenfeng; Xie, Yibin (Frontiers in Oncology, 2021)
The association between the risk factors and long-term prognosis in patients with stage II gastric cancer after radical gastrectomy has been fully revealed. The purpose of this study was to investigate the independent risk factors for treatment failure in stage II gastric cancer. Demographic, clinical, and pathological information of 247 stage II gastric cancer patients who underwent radical D2 gastrectomy in our department between January 2011 and December 2014 were collected and retrospectively analyzed. The relationship between and long-term clinical outcomes of stage II gastric cancer was analyzed using t-tests, chi-square tests, receiver operating characteristic (ROC) analysis, time-dependent ROC analysis, K–M curves, and a Cox regression model. The median follow-up of 247 stage II gastric cancer patients was 5.49 years (range: 0.12–8.62 years). The Kaplan–Meier estimated 3-year and 5-year DSS rates of the study group were 92.7% (95% CI 89.4–95.9) and 88.7% (95% CI 84.7–92.7), respectively. Higher age (>70 vs. ≤70, log-rank p = 0.0406), nerve invasion (positive vs. negative, log-rank p = 0.0133), and non-distal gastrectomy (distal partial gastrectomy vs. other surgical methods, log-rank p = 0.00235) had worse prognoses compared to controls. Univariate and multivariate analyses of disease-specific survival showed that these three factors were independent prognostic factors for patients with stage II disease. The area under time-dependent ROC curve (AUC) is 0.748 of 5-year survival and c-index is 0.696 based on the three-marker model drawn for stage II patients. Subgroup analyses showed an interaction between tumor location and nerve invasion. The age, perineural invasion, and surgical approach are independent prognostic factors for disease-specific survival after radical gastrectomy. Tumor location may be an important confounding factor for outcomes by affecting surgical methods and the hazards of nerve invasion.